ANALISIS PERSEPSI KONSUMEN TERHADAP ATRIBUT PRODUK SEPEDA MOTOR YAMAHA BERTEKNOLOGI BLUE CORE DI KOTA JAMBI - Rizwandi Rizwandi (Jurnal Dinamika Manajemen, 2016)
The purpose of this study was to explain consumer perceptions of Yamaha motorcycles with Blue Core technology in Jambi City and to analyze consumer perceptions of product attributes for Yamaha motorcycles with Blue Core technology in Jambi City. The method used in this research is research on product perceptions which is a descriptive study. The purpose of this research is to make Yamaha aware that the product attributes owned by Yamaha motorcycles with Blue Core technology which consist of product quality, product features, and product design as a whole have an important role in consumer perception. Therefore, the ideal combination of these attributes must be continuously developed in order to attract consumers to make purchases continuously. The fact was obtained that the overall average value was 4.06 from the perceptions given by consumers through questionnaires that the product attributes owned by Yamaha motorbikes with Blue Core technology in Jambi City actually received perceptions that were in the Good category (B). So it can be concluded that the attributes of Yamaha motorbikes with Blue Core technology are effective. Where Style (Style) has the highest average value of 4.31 with the very good category (SB). While Durability has the lowest value of 3.65 which means neutral or good enough.